White, slim and 100% cure, misleading health claims of nutraceuticals: a comparative study - Safuan, Sahida; Abdul Ghani Azmi, Ida Madieha; Ismail, Suzi Fadhilah; Abd. Jalil, Juriah; Daud, Mahyuddin (2018)
The slogan “Qu Puteh, Qu Puteh, Barulah Putih” and “DeHerbs, Terlajak Laris” had created a phenomenon in Malaysia. People are becoming obsessed with whitening and slimming products as well as products that claim to cure various diseases. Social media has been effectively used as a platform to market these products. It is observed that some online seller in attracting customers’ attention has advertised numerous claims. To some extent, there are sellers that claim that their product able to cure diseases that science had yet to find cure for such as cancer and diabetics. The popular marketing strategy by displaying the testimony of the users allows the producers to make profit out of the unproven claims of their products. As nutraceuticals could falls under the food category, no clinical trial is needed before marketing the product. At the end of the day, consumer is at risk of paying for a product that is overrated and may not actually benefit them. This paper aims to explore the current regulation on use of health claim in the product advertisemnt in Malaysia as well as to make comparison with other jurisdiction that is Japan. The study adopts a qualitative approach that includes doctrinal analysis and semi-structured interviews with relevant authorities. As Malaysia is aimed to be the world class-leading supplier for nutraceutical products under the Economic Transformation Programme’s Agriculture National Key Economic Area, there is a need to upgrade the local herbal supplements in the sense that any health claims must be supported by clinical evidence. Thus, a proper regulation in restraining such producers from advertising unsupported health claim is highly needed and required in protecting the consumers’ interests.